THE USE OF TECHNOLOGY IN INTENSIVE LANGUAGE TEACHING (Modern education and development, 2025)
This paper explores the role of technology in intensive language teaching, examining its benefits, challenges, and future implications. It discusses how digital tools, artificial intelligence, virtual reality, and online resources enhance engagement, personalization, and access to authentic language materials. Additionally, the paper highlights concerns such as the digital divide, overreliance on technology, misinformation, and the need for teacher training. The study concludes that while technology offers transformative potential in language learning, a balanced approach integrating traditional methods is essential for success.